Crystal structure of rilpivirine, C22H18N6. Issue 2 (20th May 2015) - Kaduk, James A.; Zhong, Kai; Blanton, Thomas N.
<x content-type="archive" xml:space="preserve">Abstract</x> The crystal structure of rilpivirine has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional techniques. Rilpivirine crystallizes in space group P21/c (#14) with a = 8.39049(3), b = 13.89687(4), c = 16.03960(6) Å, β = 90.9344(3)°, V = 1869.995(11) Å3, and Z = 4. The most prominent features of the structure are N–H···N hydrogen bonds. These form a R2, 2(8) pattern which, along with C1, 1(12) and longer chains, yield a three-dimensional hydrogen bond network. The powder pattern has been submitted to International Centre for Diffraction Data, ICDD, for inclusion in future releases of the Powder Diffraction File™.